TESTING OF BACTERIAL FILTERS AND PRESERVATIVES FOR QUALITY ASSURANCE OF LYOPHILIZED SNAIL MUCUS AS A COSMETIC COMPONENT - KHROKALO, LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Snail mucus is the popular cosmetic ingredient that is rapidly taking over the modern market of beauty industry. Conducted microbiological tests using differential diagnostic agar media showed that mucus produced by snail farms had the hazard risks of contamination with coliform bacteria and staphylococci. In order to comply with biological safety requirements and extend the shelf life of products, it is advisable to carry out fine filtration and add antiseptic substances to the mucus filtrate. Microbiological analysis of two batches of Helix aspersa lyophilized mucus was carried out after the addition of preservatives such as Sharomix 300, Lysozyme, Natamycin with Nisin and the using of microporous acetyl cellulose filters (pore diameter of 2 μm). The best results of purification were demonstrated by 1% preservative Sharomix 300 or the fine-pore bacterial filters using in combination with 0.5% Sharomix 300
Keywords: HelixComplex; lyophilized mucus; microbiological hazard risks; cosmetic product